Effects of Smartphone Addiction on Health and Academic Performance of High School Students in Ongkharak District, Nakhon Nayok Province - Chuemongkon, Wannakon; Boonnaruetee, Naruedee; Mothaniyachat, Tipakarn (Srinagarind Medical Journal, 2021)
Background and Objectives: The smartphone usages in Thai children and adolescent have been increasing nowadays, and these modern lifestyles could cause negative effects in everyday life. Accordingly, this cross-sectional descriptive study aimed to evaluate the impact of smartphone addiction on health and academic performance of high school students in Ongkharak, Nakhon Nayok. Methods: A cross-sectional descriptive study was performed by using online questionnaires which consisted of four parts including 1) general data of participants, 2) smartphone usage data using adapted questionnaires from the Thai version of smartphone addiction scale short version (SAS-SV), 3) physical health data using adapted questionnaires from Chuemongkon’s physical health assessment, and 4) mental health data using Thai version of the Children’s Depression Inventory (CDI) for depression data and Thai version of the Self-Rating Anxiety Scale (SAS) for anxiety data. Results: This study was conducted in 432 participants. Most of them (59.3%) were girls and mean age of 14.6 years old. The duration and frequency of smartphone using of most participants were 3-4 hours/day and 11-20 times/day, respectively. The results revealed that 42.1% of students were smartphone addiction. The impact of smartphone addiction on health and academic performance showed that smartphone addiction was related to overall physical health, visual health, hearing health, depression and anxiety (p = <0.001, 0.020, 0.001, 0.001 and 0.003, respectively). There was no effect of smartphone addiction on academic performance. Conclusion: The smartphone addiction impacted on overall physical health and mental health, including depression and anxiety but it had no effect on academic performance of high school students in Ongkharak, Nakhon Nayok.